Heirs Lose Legal Protection When Land is Planned for Road Development in Indonesia - Jestika Erika Lambonan; Rasji Rasji (Academia Open, 2025)
General Background: Public infrastructure planning in Indonesia frequently triggers conflict between state development interests and private inheritance rights. Specific Background: The designation of inherited land for road development often occurs before heirs complete formal registration processes, creating uncertainty in their legal standing. Knowledge Gap: Despite clear expropriation requirements under the Basic Agrarian Law and the Land Acquisition Act, limited research examines how planning designations are misinterpreted to extinguish heirs’ rights without compensation. Aim: This study analyzes the extent of legal protection available to heirs when inherited land is included in a road-planning area, using a normative juridical approach and the Jakarta High Court Decision No. 225/PDT/2019 as a case study. Results: Findings show that planning documents are sometimes treated as automatically converting inherited land into state land, contrary to statutory due-process requirements, thereby depriving heirs of compensation and recognition. Novelty: The article exposes a critical doctrinal inconsistency in judicial reasoning and compares it with foreign eminent-domain standards that more robustly protect succession-based property rights. Implications: Strengthening heir verification, clarifying administrative procedures, and reforming land-acquisition governance are imperative to uphold constitutional property guarantees and prevent substantive injustice. Highlights: Highlights how road development planning can erode heirs’ legal protection before formal expropriation and compensation. Critically analyzes a Jakarta High Court decision that treats planned-road designation as automatically converting inherited land into state land. Proposes reforms such as mandatory heir verification and clearer procedures to align land acquisition with constitutional property guarantees. Keywords: Legal Protection, Heirs’ Rights, Land Acquisition, Road Development, State Land